2008
DOI: 10.1007/s00432-008-0442-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum vascular endothelial growth factor: a prognostic factor in cervical cancer

Abstract: Purpose To study pre-treatment serum VEGF of patients with invasive cervical cancer and its possible role as prognostic indicator. Methods VEGF was measured using ELISA in the largest patient group (n = 167) to date. Reults Serum VEGF was signiWcantly higher in advanced tumor stage (P = 0.01), large tumor size (tumors larger than 2 cm) (P = 0.03), and the presence of vascular space invasion (P = 0.05). Serum VEGF was associated with disease free and overall survival [DFS: Hazard Ratio (HR) = 2.61; 95% CI 1.32-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
3
21
1
2
Order By: Relevance
“…It promotes the proliferation of vascular endothelial cells and angiogenesis (Lv et al, 2010). Serum VEGF-A is highly elevated in several types of cancer including colon (De Vita et al, 2004), cervix (Zusterzeel et al, 2009), breast and gynaecological cancer (Koukourakis et al, 2011), non-small cell lung cancer (Liang et al, 2013) and prostate (Singh et al, 2013). In our study, serum VEGF-A level was found to be significantly higher (p=0.001) in SCCHN patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It promotes the proliferation of vascular endothelial cells and angiogenesis (Lv et al, 2010). Serum VEGF-A is highly elevated in several types of cancer including colon (De Vita et al, 2004), cervix (Zusterzeel et al, 2009), breast and gynaecological cancer (Koukourakis et al, 2011), non-small cell lung cancer (Liang et al, 2013) and prostate (Singh et al, 2013). In our study, serum VEGF-A level was found to be significantly higher (p=0.001) in SCCHN patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 50%
“…Our results are similar to the findings of previous study by Shang et al (2002) in oral squamous cell carcinoma. However, Bachtiary et al (2002) and Zusterzeel et al (2009) did not find any significant correlation between stage of disease and serum VEGF-A level in carcinoma of cervix.…”
Section: Serum Vegf-a Level and Treatment Responsementioning
confidence: 62%
“…(Srivastava et al, 2009). Another study of Zusterzeel et al, which got a similar conclusion, detected serum VEGF levels in 167 cervical cancer patients and found that serum VEGF levels, which were significantly correlated with tumor stage, tumor size and vascular compartment infiltration, had a significant impact on disease free survivals and overall survivals of the patients, and further multivariate COX regression analysis showed that serum VEGF levels were prognostic factors of cervical cancer (Zusterzeel et al, 2009). However, the study of Katanyoo et al showed that median serum VEGF level before treatment was 611.3 pg/ mL, which was irrelevant to tumor stage, histological type, tumor size etc.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, tumor cells can proliferate for two potential reasons: on the one hand, an intrinsic response to intermittent hypoxia could be sensed at the tumor level; on the other, tumor growth could be boosted by increased vascularization, enhanced by external factors such as VEGF which reach the tumor via the blood stream [31,38]. In fact, circulating VEGF is used as a cancer prognostic marker [31,39,40] and some direct inhibitors of the VEGF pathway are currently approved for use in cancer therapy [41]. This pathway could be of particular relevance in OSA since patients with this sleep breathing disorder exhibit increased VEGF in the bloodstream [16,19,20].…”
Section: Discussionmentioning
confidence: 99%